2012
DOI: 10.1007/s13238-011-1127-x
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between autophagy and apoptosis: where does this lead?

Abstract: Recent advances in the understanding of the molecular processes contributing to autophagy have provided insight into the relationship between autophagy and apoptosis. In contrast to the concept of "autophagic cell death," accumulating evidence suggests that autophagy serves a largely cytoprotective role in physiologically relevant conditions. The cytoprotective function of autophagy is mediated in many circumstances by negative modulation of apoptosis. Apoptotic signaling, in turn, serves to inhibit autophagy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
230
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(238 citation statements)
references
References 73 publications
(104 reference statements)
7
230
1
Order By: Relevance
“…10,13,14 Whereas many studies have focused on the modulation of autophagy by apoptotic-signaling pathways, it is also clear that autophagy can regulate apoptosis. 4 In the present study, we have found that, post-TBI, moderate hypothermia could increase expression of autophagy and attenuate hippocampal cell death, which may suggest that the autophagy pathway may play an important role in the neuroprotective function of moderate hypothermia.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…10,13,14 Whereas many studies have focused on the modulation of autophagy by apoptotic-signaling pathways, it is also clear that autophagy can regulate apoptosis. 4 In the present study, we have found that, post-TBI, moderate hypothermia could increase expression of autophagy and attenuate hippocampal cell death, which may suggest that the autophagy pathway may play an important role in the neuroprotective function of moderate hypothermia.…”
Section: Discussionsupporting
confidence: 55%
“…3 Macroautophagy (hereafter referred to as autophagy) is a catabolic process in which cells degrade their own components by enveloping them in double-membrane vesicles referred to as autophagosomes that are then targeted for lysosomal degradation. 4 Recently, a series of studies has reported the increase of autophagy in subarachnoid hemorrhage, intracerebral hemorrhage, hypoxia-ischemia, neurodegenerative disease, and TBI. [5][6][7][8][9][10] However, the function of autophagy in TBI remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy supports cell survival in many circumstances; this cytoprotective role of autophagy is especially important upon nutrient withdrawal. 37 In T lymphocytes, autophagy is indispensible not only for surviving growth factor withdrawal, but also for regulating the mitochondria and endoplasmic reticulum. 31,38,39 How autophagy promotes cell survival in c-FLIP L À / À T cells remains to be determined.…”
Section: Necroptosis In C-flip L -Deficient T Cells Involves Reactivementioning
confidence: 99%
“…30 Therefore, the expression levels of Bcl-2, Bcl-XL and Mcl-1 were investigated by western blot in CEM-R and CEM-S cells. Although we did not detect major differences between Bcl-2 and Mcl-1, Bcl-XL was expressed to a much higher extent in CEM-R when compared with CEM-S cells (Supplementary Figure S1).…”
Section: Mk-2206 Induces Autophagymentioning
confidence: 99%